Modeling and Empirical Analysis of Regional Tourism Competitiveness Based on Niche Theory - Yingjuan Yang; Yanxia Wu; Haiqing Hu (Discrete Dynamics in Nature and Society)
The fierce competition in tourism has brought a string of problems, such as the homogeneous development of regional tourism resources and the escalation of regional competition. One key issue in urban tourism today is how to identify competitors, recognize own advantageous resources, and clarify the direction of development. This paper evaluates the competitiveness of regional tourism in three steps: setting up an evaluation system, calculating niche and niche overlap, and conducting synthesis and cluster analysis. Firstly, a comprehensive evaluation system of urban tourism niche was established, which includes such four dimensions as tourism resources, tourism market, social economy, and eco-environment, and the weight of each index was calculated by entropy method. Next, regional niche and niche overlap were computed by niche theory. Taking the mean of niche overlap and that of composite niche as the references, the authors drew an overall distribution map of regional tourism niche. After that, a cluster analysis was carried out with the four-dimensional niche and composite niche of regional tourism. Finally, an empirical analysis was performed on the tourism competitiveness in ten prefectures of Shaanxi Province, using the data in 2010–2018. The results show that the prefectures differed greatly in tourism development and competed fiercely against each other.